Theoretical and Experimental Studies of Seismoelectric Conversions in Boreholes (Communications in Computational Physics, 2008)
We present theoretical and experimental studies on the effects of formationproperties on seismoelectric conversions in fluid-filled boreholes. First, we derive thetheoretical formulations for seismoelectric responses for an acoustic source in a borehole. Then, we compute the electric fields in boreholes penetrating formations withdifferent permeability and porosity, and then we analyze the sensitivity of the converted electric fields to formation permeability and porosity. We also describe the laboratory results of the seismoelectric and seismomagnetic fields induced by an acoustic source in borehole models to confirm our theoretical and numerical developmentsqualitatively. We use a piezoelectric transducer to generate acoustic waves and a pointelectrode to receive the localized seismoelectric fields in layered boreholes and theelectric component of electromagnetic waves in a fractured borehole model. Numerical results show that the magnitude ratio of the converted electric wave to the acousticpressure increases with the porosity and permeability increases in both fast and slowformations. Furthermore, the converted electric signal is sensitive to the formationpermeability for the same source frequency and formation porosity. Our experimentsvalidate our theoretical results qualitatively. An acoustic wave at a fracture intersecting a borehole induces a radiating electromagnetic wave.